2022
DOI: 10.26803/ijlter.21.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Elementary Teachers’ Readiness in Delivering Sex Education amidst Covid-19 pandemic

Abstract: The emergence of variants of Covid-19, the persistence of lockdowns in many countries, and the necessity to maintain sustainable education have resulted in a shift from the traditional classroom to virtual space. As such, there is a strong need to leverage technological advances while mitigating the challenges faced by primary teachers. Through the incorporation of eight elements, the authors sought to better understand factors that influence teacher readiness to deliver sex education in primary schools. Struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Of the many techniques available for PLS-SEM [41], [42], the authors utilized the Generalized Structured Component Analysis (GSCA) due to its flexibility to work with even small samples [43], [44]. GSCA has been applied in various domains [37], [38], [45]. GSCA Pro 1.1 [46] was used to conduct the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the many techniques available for PLS-SEM [41], [42], the authors utilized the Generalized Structured Component Analysis (GSCA) due to its flexibility to work with even small samples [43], [44]. GSCA has been applied in various domains [37], [38], [45]. GSCA Pro 1.1 [46] was used to conduct the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Policy: This factor refers to a set of protocol and procedures to follow within an organization or institution [38], [39]. Yang et al [39] reported that policy played a crucial role in prefabricated digital transformation of innovative ecosystem.…”
Section: Hypothesis 6 Facilitating Conditions Will Have Positive Impa...mentioning
confidence: 99%
“…The students of the modern institutions are more dependent on the innovative teaching approach because they believe that with new world learning methods, their performance would be increased (Brubaker and Beverly, 2020 ). However, if the teachers help the students for developing abstract conceptualization, it would be great for the students to learn new things in an alternative way (Niedzwiedz et al, 2021 ; Laletina et al, 2022 ; Nguyen et al, 2022 ). Therefore, educational institutions need to improve the quality of education and training in the learning performance of the students.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, this study aims to provide a clear picture of the students' learning performance and the factors that are influencing in it the modern world. Moreover, this study also emphasizes determining the important role of teaching innovation and abstract conceptualization to determine the influence of these factors on the critical learning performance of the students as discussed in the study of Nguyen et al (2022). Furthermore, this study is designed to provide a significant contribution to teaching innovation as a mediator between the relationships among active experimentation, abstract conceptualization, reflective observations, and students' learning performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is noted that Chinese students are not provided with innovative physical education because of specific inabilities held by both government and other stakeholders ( Kuk and Holst, 2018 ; Wanaratna et al, 2019 ). Therefore, it is the fundamental right of Chinese students to get innovative physical education in a different alternative way to develop their learning capacity and improve their mental state for better productivity related to human instinct ( Nguyen et al, 2022 ). Besides men, Chinese female physical education students must also be equipped with the required innovative learning opportunities to prepare better to cater to the opportunities posed by the environment ( Lee, 2018 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%